The Neutrality of Civil Servants in The 2024 Elections - Ismarini Della Purnama; Novaranty Zura Dwiputri; Kaharuddin; Anni Alvionita (Veteran Law Review, 2025)
The neutrality of civil servants (Aparatur Sipil Negara/ASN) is a fundamental principle in ensuring fair and democratic elections in Indonesia. Despite clear regulations under the 1945 Constitution, the Civil Service Law, and the Election Law, violations of neutrality among ASN have persisted, raising concerns over the balance between bureaucratic impartiality and the political rights of civil servants. This study aims to analyze whether administrative sanctions imposed on ASN for political involvement during the 2024 elections are proportionate in light of constitutional guarantees of political rights. Employing a normative legal research method with a statute, conceptual, and case approach, this paper examines relevant laws, constitutional provisions, and judicial decisions, including rulings from the Constitutional Court and Administrative Courts. The findings reveal that, while sanctions are necessary to preserve electoral integrity, their application often lacks proportionality, with cases of dismissal for minor infractions highlighting inconsistencies and potential over-restriction of fundamental rights. The proportionality test, widely recognized in constitutional law, provides a useful framework to assess whether restrictions on ASN’s political rights serve legitimate aims, are necessary, and remain balanced. The study concludes that proportional application of administrative sanctions, combined with clearer regulatory guidelines and stronger appeal mechanisms, is essential to uphold both democratic values and the protection of civil servants’ constitutional rights.